VARIABEL INTERNAL DAN EKSTERNAL TERHADAP KINERJA KEUANGAN DAN NILAI PERUSAHAAN SEKTOR PERBANKAN - Harry Patuan Panjaitan (Jurnal Keuangan dan Perbankan, 2011)
This research aimed at analyzing and testing the effect of the internal variable and external variable tofinancial performance and corporate value. This study used quantitative and qualitative methods. The resultsof this study were as follows: (1) market concentration, interest rate, and banking penetration variable whichpotentially created high financial performance; exchange rate having a high power to push financial performance.(2) Capital, liquidity and composition of low interest fund having high power to improve financialperformance; asset productivity and total asset that did not have an impact to financial performance; employeeproductivity and efficiency that had an impact to financial performance. (3) Financial performance that hadnot been capable to improve corporate value. (4) concentration variable which had not been capable of improvingcorporate value; exchange rate, interest rate, and banking penetration which had an impact to corporatevalue. (5) capital, liquidity, productivity of asset, total asset, efficiency and quality of credit variable whichwere potentially to improve corporate value; composition of low interest fund having a high power to pushcorporate value; productivity of employee having a great power to improve corporate value.